2021
DOI: 10.3390/molecules26092472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Antifungal Potential of Botanical Compounds to Control Botryotinia fuckeliana and Rhizoctonia solani

Abstract: The European Union is promoting regulatory changes to ban fungicides because of the impact their use has on the ecosystem and the adverse effects they can pose for humans. An ecofriendly alternative to these chemicals to fight against fungal species with low toxicity is essential oils and their compounds extracted from aromatic plants. The purpose of this study was to evaluate the in vitro antifungal capacity of the botanical compounds eugenol, carvacrol, thymol, and cinnamaldehyde, and the synergy or antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In this concept, the volume density of the colonies was firstly assessed using ImageJ software (National Institutes of Health, Bethesda, MD, USA), counting the points of the stereological grid hitting the colonies and those falling to the reference space (growth substrate used, i.e., bread). The antifungal activities of the EOs were expressed as the percentage of mycelial growth inhibition (MGI), which was calculated using the formula: MGI = [(C − T)/C] × 100 [71], where C = volume density of the fungal colony in the control group and T = volume density of that in the treatment group.…”
Section: In Situ Antifungal Analyses On Bread Modelmentioning
confidence: 99%
“…In this concept, the volume density of the colonies was firstly assessed using ImageJ software (National Institutes of Health, Bethesda, MD, USA), counting the points of the stereological grid hitting the colonies and those falling to the reference space (growth substrate used, i.e., bread). The antifungal activities of the EOs were expressed as the percentage of mycelial growth inhibition (MGI), which was calculated using the formula: MGI = [(C − T)/C] × 100 [71], where C = volume density of the fungal colony in the control group and T = volume density of that in the treatment group.…”
Section: In Situ Antifungal Analyses On Bread Modelmentioning
confidence: 99%
“…The extracts in water and all organic solvents has shown strong potency of A. alleaceum leaf extract which can be used as a potent botanical fungicide in controlling fruit fungal pathogen after harvest, during storage and transportation. Recent findings on the effectiveness of essential oils such as biodegradable and ecofriendly fungitoxicants have shown the potential for their exploitation as a natural fungicide (Nigam et al, 2021;Sempere et al, 2021;Tripathi et al, 2021). The fungal activity of oils found in Ocimum, Thymus, Origanum, Anethum, Eucalyptus, Foeniculum and Citrus against several post-harvest germs reveal the marked fungicidal activity of carvacrol (thyme, origanum oil) and p-anisaldehyde (anethol Aqueous plant extract and Essential oil treatment Days oxidation products in anise oil) (Caccioni and Gizzardi 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Vokou et al [ 139 ] claimed that volatile oils extracted from Satureja thymbra could reduce the spore germination and mycelial growth of Penicillium citrinum and Mucor hiemalis , respectively. Another study conducted by Sempere-Ferre et al [ 152 ] showed that EO constituents, either alone or in combination, inhibited the mycelial growth of Botryotinia fuckeliana and Rhizoctonia solani , although eugenol exerted a fungistatic effect only. Similarly, testing the antifungal efficacy of various EO constituents, Marei et al [ 153 ] found that 1,8-cineole, (R)-camphor, (R)-carvone, camphene, cuminaldehyde, (R)-linalool, geraniol, (1R,2S,5R)-menthol, (S)-fenchone, myrcene, thymol, and (S)-limonene were promising substances against Fusarium oxysporum , Penicillium digitatum , Aspergillus niger , and Rhizoctonia solani .…”
Section: Aromatic Plants As Biocontrol Agentsmentioning
confidence: 99%